“Heresy against the Church”: I. A. Mohler and A. S. Khomyakov as polemicists - Anna Titova (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article compares and analyses the anti-Protestant polemic of A. S. Khomyakov presented in three well-known polemic brochures and the criticism of heresy in the “Unity in the Church” by A. Möhler. The relevant literature has repeatedly noted the affi nity of ecclesiological views of both thinkers. Despite the fact that in his polemic Khomyakov never refers to Möhler, the similarity of their argumentation suggests that he relied on it. The texts of both authors obviously diff er in genre, structure, tasks, but this makes the similarity of their polemic principles and techniques even more vivid. The purpose of this article is to identify, reconstruct and compare the internal logic of the authors’ polemic: their arguments and basis, the object of their criticism, the structure of their arguments. The study shows the similarity in the structure and content of their debate based on the shared ecclesiological premises and romantic views. The opposition of church as love and heresy as separation from love which they propose is, on the one hand, in the framework of the ancient church polemic and, on the other hand, is reconsidered in the categories of romantic idealism.